Kliničko – patološka analiza oštećenja bubrega kod bolesnika sa nefrotskim sindromom u Republici Srpskoj - Mrgud, Jasmina; Gašić, Branislav; Vlatković, Vlastimir; Topić, Goran (Scripta Medica, 2022)
Background / Aim: Nephrotic syndrome (NS) is a clinical syndrome characterised by massive proteinuria > 3.5 g in 24 h urine, hypoalbuminaemia, hyperlipidaemia and oedema. Aim of this study was to determine the aetiology and frequency of kidney diseases that occur as the cause of NS in adults in the Republic of Srpska and the progression of renal insufficiency, disease outcomes and efficacy of applied therapy.Methods: The retrospective study included patients aged 18 to 80 hospitalised between 2014 and 2018 due to clinically and laboratory-manifested NS. In patients with suspected primary glomerular disease, a kidney biopsy with immunofluorescent dyeing was performed. The first examination involved hospital admission and the next check-up six months after the first hospitalisation. Basic clinical parameters were followed: creatinine, clearance creatinine, albumin, total protein, cholesterol, total protein in 24 h urine and microscopy of urine during the first hospitalisation and repeated same laboratory findings on control. The progression of kidney failure during this period was assessed, as well as the efficacy of immunosuppressive therapy.Results: In primary NS category membranous glomerulonephritis (MGN) was present at 40.7 % of patients, followed by focal segmental glomerulosclerosis (FSGS) 21.7 %, membranoproliferative glomerulonephritis (MPGN) 11.9 % and IgA glomerulonephritis (IgAN) 11.9 %. Nephroangiosclerosis was verified as the most common cause of secondary NS with 28.8 % and lupus nephritis 21.2 %, followed by ANCA-associated GN (11.5 %) and diabetic nephropathy (11.5 %). Thirty-four patients (21 %) died during the follow-up. Thirty-four patients (18.6 %) progressed to end stage renal disease during the five-year follow-up.Conclusion: The pathology of kidney disease in older patients is often very complex; therefore, a kidney biopsy should be conducted at an early stage of kidney disease for the purpose of obtaining an accurate diagnosis, determining appropriate treatment and thus improving the prognosis of the patient.